The Identification of Online Strategy Learning Results While Students Learn from Home During the Disruption of the COVID-19 Pandemic in Indonesia - SUDARMO; NUGRAHA, MULYAWAN SAFWANDY; MARDHIAH; LIOW, FESTUS EVLY R.I.; ASLAN (The journal of contemporary issues in business and government, 2021)
This study aimed to identify a strategic learning approach to support student learning development from home, resulting from school closures policy due to the disruption of the COVID-19. Many studies have shown that learning success at home during a pandemic is closely related to students' learning outcome orientation strategies. To understand what approach can support this learning, we have reviewed various related literature. After the review completed, in- depth analysis and interpretation were with a descriptive design on pedagogical competence, motivation, materials, methods, and evaluation of success. Connected with teaching experiences, theories, and student learning realities from home so far, finally, we can identify efforts to develop strategic designs to support student learning from home as follows: 1) learning mindset and ownership, 2) situational awareness, 3) vision and learning innovation, 4) collaborative learning, 5) critical thinking skills, 6, 7) high commitment, 8) new learning skills, 9) knowledge resources, 10) independent learning management, 11) academic competency innovation, and 12) learning balance. These findings are valid and reliable because they have answered the research question. Therefore, these findings can serve as a relevant solution to support students learning from home while waiting for schools to reopen.